Integrating Augmented Reality Based Comics into Chemical Bonding Instruction to Enhance Students’ Thinking Skills - Risqah Amaliah Kasman; Muhammad Fuad; Hastuti Agussalim; Imranah Imranah; Muhamad Fadli; Nudia Tuljannah; Siti Yasya Ey Fathanah (Jurnal Penelitian Pendidikan IPA, 2026)
This study aims to investigate the effectiveness of integrating Augmented Reality (AR)-based comics into chemical bonding instruction to enhance students’ critical thinking skills. A quasi-experimental design with a non-equivalent control group was employed, involving 40 eleventh-grade students divided into an experimental group and a control group. The experimental group was taught using AR-based comics within a project-based learning framework, while the control group received conventional instruction without AR support. Data were collected through essay tests, observation sheets, and documentation, and analyzed using descriptive statistics, N-gain, and an independent sample t-test. The results indicate that the experimental group achieved a higher post-test mean score (75.75) compared to the control group (65.30). The N-gain score of the experimental group (0.49) was categorized as moderate, exceeding that of the control group (0.29), which was classified as low. Statistical analysis revealed a significant difference between the two groups (p < 0.05). These findings suggest that the integration of AR-based comics effectively enhances students’ critical thinking skills by facilitating visualization, engagement, and conceptual understanding. Therefore, this approach can serve as an innovative instructional strategy to improve the quality of chemistry learning.